2015
DOI: 10.1590/0100-83582015000200017
|View full text |Cite
|
Sign up to set email alerts
|

Volatility of Different Formulations of Clomazone Herbicide

Abstract: -Volatilization represents an important process in the displacement of pesticides for the environment. The physicochemical properties of the clomazone molecule indicate its relative volatility. Therefore, this study was carried out to assess the volatilization of different clomazone herbicide formulations using bioindicator species. To that end, airtight glass boxes were used with the presence of different clomazone formulations and plant species. The formulations used were Gamit 360 CS ®

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 13 publications
(9 reference statements)
3
16
0
Order By: Relevance
“…(Figures 2 and 3), mainly in the plants grown near the herbicide application site (1 m away). These results corroborate those found by Schreiber et al, (2015), who evaluated volatilization of three clomazone formulations in a greenhouse and observed that Gamit 360 CS ® caused less injury to the indicator plant species. In other study conducted by Keifer et al (2007), also in controlled conditions, it was determined that volatilization of microencapsulated clomazone formulations was 16% lower than the total volatilization of an emulsified concentrated formulation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…(Figures 2 and 3), mainly in the plants grown near the herbicide application site (1 m away). These results corroborate those found by Schreiber et al, (2015), who evaluated volatilization of three clomazone formulations in a greenhouse and observed that Gamit 360 CS ® caused less injury to the indicator plant species. In other study conducted by Keifer et al (2007), also in controlled conditions, it was determined that volatilization of microencapsulated clomazone formulations was 16% lower than the total volatilization of an emulsified concentrated formulation.…”
Section: Resultssupporting
confidence: 90%
“…However, after this period, the plants continued growing and developing, with new leaves growing without apparent symptoms. Schreiber et al (2015) found, in controlled environment, practically the same levels of toxicity of this study at 10 DAH, indicating similarity with the field results. However, at 24 DAH, the same authors reported high levels of injury, without recovery of the plants, possibly because it was a closed environment, not enabling the herbicide dissipation in the environment, a situation not found in the field conditions.…”
Section: Resultssupporting
confidence: 89%
“…Volatilization can be assessed by using micrometeorological system (Majewski, 1999), field and semi-field conditions (Van den Berg et al, 1999), closed-chambers (Schreiber et al, 2013;Schreiber et al, 2015) and wind tunnels (Bedos et al, 2002b).…”
Section: Volatilizationmentioning
confidence: 99%
“…Bioindicator plants can be used to evaluate the volatility risk of a herbicide in closed-chambers and/or field conditions (Schreiber et al, 2013;Schreiber et al, 2015;Schreiber et al, 2016). Herbicides concentrations in air are evaluated by the symptoms caused on the bioindicator plants, which are used instead of atmospheric measurements and analytical analysis (Lam and Gray, 2003).…”
Section: Volatilizationmentioning
confidence: 99%
See 1 more Smart Citation